Editor-in-Chief's welcome to Hepatology, Medicine and Policy. Issue 1 (December 2016) - Lazarus, Jeffrey
Abstract Hepatology, Medicine and Policy (HMAP ), a new open-access peer-reviewed journal, is making its debut at a time when the hepatitis field is seeing great progress but still has far to go. The World Health Organization and many countries have shown increasing interest in viral hepatitis in recent years, helping to foster a stronger response to this group of diseases. Meanwhile, alcohol-associated cirrhosis and alcohol-associated liver cancer continue to take a heavy toll worldwide, as does non-alcoholic fatty liver disease. The lack of a unified strategic response to viral hepatitis and other liver diseases is the impetus for launchingHMAP, which will publish policy, public health and social science articles alongside clinical science articles. It will encourage submissions in diverse domains such as disease prevention and management, epidemiology, economics, health behavior, health service delivery, ethics, human rights, and the role of laws, policies and clinical guidelines in shaping health initiatives. The current attention to powerful new hepatitis C treatments presents a strategic opportunity to more comprehensively address the full constellation of biomedical and social issues relating to liver health.HMAP is committed to publishing research and policy articles that help to drive forward this broader agenda.